Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Let's solve the given equation step-by-step to find and correct any mistakes.
### Original Equation:
[tex]\[ 6x - 1 = -2x + 9 \][/tex]
### Step-by-Step Solution:
1. Combine like terms on both sides of the equation:
Add [tex]\(2x\)[/tex] to both sides to get all terms with [tex]\(x\)[/tex] on the left side:
[tex]\[ 6x - 1 + 2x = -2x + 9 + 2x \][/tex]
Simplifying, we get:
[tex]\[ 8x - 1 = 9 \][/tex]
2. Isolate the term with [tex]\(x\)[/tex]:
Add 1 to both sides to move the constant term to the right side:
[tex]\[ 8x - 1 + 1 = 9 + 1 \][/tex]
Simplifying, we get:
[tex]\[ 8x = 10 \][/tex]
3. Solve for [tex]\(x\)[/tex] by dividing both sides by 8:
[tex]\[ x = \frac{10}{8} \][/tex]
4. Simplify the fraction:
[tex]\[ x = \frac{10}{8} = \frac{5}{4} \][/tex]
### Identifying the Mistake:
1. Given Steps:
[tex]\[ \begin{aligned} 6x - 1 & = -2x + 9 \\ 8x - 1 & = 9 \\ 8x & = 10 \\ x & = \frac{8}{10} \\ x & = \frac{4}{5} \end{aligned} \][/tex]
2. Step 3:
The step where we solve [tex]\(8x = 10\)[/tex] by dividing both sides by 8 should give:
[tex]\[ x = \frac{10}{8} \][/tex]
This step is correctly performed (although the simplification afterward is incorrect).
3. Step 4:
The simplification of [tex]\(x = \frac{10}{8}\)[/tex] was incorrectly shown as [tex]\( \frac{4}{5} \)[/tex]. The correct simplification is:
[tex]\[ x = \frac{5}{4} \][/tex]
Thus, the correct answer is:
C. Step 3 is incorrect and should be [tex]\( x = \frac{10}{8} \)[/tex].
To summarize: The mistake in the solution is in the simplification of the fraction in Step 3. It should be [tex]\( x = \frac{10}{8} \)[/tex] and simplify to [tex]\( \frac{5}{4} \)[/tex], not [tex]\( \frac{4}{5} \)[/tex].
### Original Equation:
[tex]\[ 6x - 1 = -2x + 9 \][/tex]
### Step-by-Step Solution:
1. Combine like terms on both sides of the equation:
Add [tex]\(2x\)[/tex] to both sides to get all terms with [tex]\(x\)[/tex] on the left side:
[tex]\[ 6x - 1 + 2x = -2x + 9 + 2x \][/tex]
Simplifying, we get:
[tex]\[ 8x - 1 = 9 \][/tex]
2. Isolate the term with [tex]\(x\)[/tex]:
Add 1 to both sides to move the constant term to the right side:
[tex]\[ 8x - 1 + 1 = 9 + 1 \][/tex]
Simplifying, we get:
[tex]\[ 8x = 10 \][/tex]
3. Solve for [tex]\(x\)[/tex] by dividing both sides by 8:
[tex]\[ x = \frac{10}{8} \][/tex]
4. Simplify the fraction:
[tex]\[ x = \frac{10}{8} = \frac{5}{4} \][/tex]
### Identifying the Mistake:
1. Given Steps:
[tex]\[ \begin{aligned} 6x - 1 & = -2x + 9 \\ 8x - 1 & = 9 \\ 8x & = 10 \\ x & = \frac{8}{10} \\ x & = \frac{4}{5} \end{aligned} \][/tex]
2. Step 3:
The step where we solve [tex]\(8x = 10\)[/tex] by dividing both sides by 8 should give:
[tex]\[ x = \frac{10}{8} \][/tex]
This step is correctly performed (although the simplification afterward is incorrect).
3. Step 4:
The simplification of [tex]\(x = \frac{10}{8}\)[/tex] was incorrectly shown as [tex]\( \frac{4}{5} \)[/tex]. The correct simplification is:
[tex]\[ x = \frac{5}{4} \][/tex]
Thus, the correct answer is:
C. Step 3 is incorrect and should be [tex]\( x = \frac{10}{8} \)[/tex].
To summarize: The mistake in the solution is in the simplification of the fraction in Step 3. It should be [tex]\( x = \frac{10}{8} \)[/tex] and simplify to [tex]\( \frac{5}{4} \)[/tex], not [tex]\( \frac{4}{5} \)[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.